Characterizations of MWCNTs nanofluids on the effect of surface oxidative treatments - Abdullah, Norli; Norizan, Mohd Nurazzi; Janudin, Nurjahirah; Mohd Kasim, Noor Azilah; Mohd Saidi, Norshafiqah; Osman, Mohd Junaedy; Mohamad, Imran Syakir (MDPI, 2022)
In this study, multi-walled carbon nanotubes (MWCNTs) were chemically modified using three acid treatment methods to introduce the surface oxygen functional group (SOFG). The presence of SOFG on the MWCNTs has been characterized by Fourier Transform Infrared (FTIR) spectroscopy. Morphology, structural and thermal properties were performed using Field Emission Scanning Electron Microscopy (FESEM), Raman spectroscopy, and Thermogravimetric analysis (TGA), respectively. The result shows that the modification with acid treatment significantly affects the degree of defects and surface group functionality of surface oxidized MWCNTs from method B. The preparation of nanofluids using MWCNTs produced from method B (MWCNT-MB) was prepared using two different parameters: with and without polyvinylpyrrolidone (PVP) as surfactant. The experiment was conducted by setting variable carbon particle concentration from 0.1 wt.% to 1.0 wt.%, and the amount of PVP is 10% of carbon particles at different temperatures (6 ◦C, 25 ◦C, 40 ◦C). Based on visual observation, the dispersion of carbon particles was enhanced by the presence of PVP as the stabilizing agent. The thermal conductivity performance of nanofluids revealed that the surface oxidized MWCNTs with PVP show enhanced thermal conductivity compared to the nanofluid containing MWCNTs without PVP. The improvement contributes to this in terms of stability and homogenization of nanoparticles. Hence the improved distribution of MWCNTs in water-based media improves thermal conductivity. These promising properties of MWCNTs in water-based fluids would enable the nanofluids to be used in heat transfer fluid and cooling applications.